The diagnosis and treatment of plantar fasciitis - Levenets, Vitaliy; Osadchaya, Lyudmila (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The overload syndrome, accompanied with some thickening of the plantar fascia, was revealed in 50 of 60 clinically and ultrasonographically examined sportsmen. The plantar fascia thickness did not correlate with the size of a calcaneal “spur” and did not cause pains in the sportsmen. The application of high-power shock-wave therapy with MINILIT SL-1 and PIEZOWAN-100 devices during 2 years significantly reduced the pain and made it possible to go on participating in trainings and competitions.